The linkages between internationalization and environmental strategies of multinational construction firms. (10th March 2016) - Chen, Po-Han; Ong, Chuan-Fang; Hsu, Shu-Chien
Abstract: Multinational construction firms have increasingly engaged in more environmental management activities, however the relationship between internationalization performance and environmental proactivity remains unaddressed. The purpose of this study is to explore the linkage between internationalization and environmental strategy. The study posits that firms deploying a higher tier of environmental strategy correlate with higher degrees of internationalization. The sample of construction firms were drawn from the Engineering News-Record Top International Contractor list. Environmental information of each sample member was extracted through content analysis. Based on previous resource-based view studies, a schema of three clusters of environmental strategies was constructed to depict reactive, preventive, and proactive postures in strategic environmental management. Degree of internationalization is measured as investment intensity, geographical extensity, and geographical concentration. The results indicate that construction firms that are proactive in strategic environmental management exhibit greater internationalization up to an extent, where additional proactivity then no longer correlates with further heightened internationalization. In addition, the results present some preliminary findings on how multinational construction firms deploy strategic environmental capabilities, shedding light on internationalization portfolios across developed and developing regions. Highlights: Three environmental strategies of multinational construction firms are identified. Environmental proactivity strengthens competitive advantages in internationalization. Firms pursuing reactive strategy would be laggard in internationalization. Preventive strategy promotes network spread in developed and developing countries. Proactive strategy promotes regional diversification in developed countries.